Effect of radio-frequency treatment on quality of dates (Phoenix dactylifera L. cv. Deglet Nour) - Nourani, Ahmed; Pegna Francisco, Garbati; Khadidja, Benahmed (Journal of Scientific Agriculture, 2017)
Algeria’s date palm (Phoenix dactylifera L) fruit is one of the most important exported products from non hydrocarbon sources. As other fresh or dry fruits, the dates (cv. Deglet Nour) are exposed to damage during storage. In our study, we will apply a postharvest treatment using a radiofrequency radiation as a new technique used on dates while evaluating its effect on date palm fruit quality. The results obtained reveal that the treatment was effective on the capacity of dates to maintain their pH, moisture content and ash percentage during the storage compared with the dates untreated. Likewise, it achieved complete disinfection of dates. As results, the radiofrequency presents a practical alternative to the actually techniques used on postharvest treatment.